2009
DOI: 10.1021/tx800405v
|View full text |Cite
|
Sign up to set email alerts
|

Products of Oxidative Stress Inhibit Aldehyde Oxidation and Reduction Pathways in Dopamine Catabolism Yielding Elevated Levels of a Reactive Intermediate

Abstract: Dopamine (DA) has been implicated as an endogenous neurotoxin to explain the selective neurodegeneration as observed for Parkinson’s disease (PD). In addition, oxidative stress and lipid peroxidation are hypothesized culprits in PD pathogenesis. DA undergoes catabolism by monoamine oxidase (MAO) to 3,4-dihydroxyphenylacetaldehyde (DOPAL), which is further oxidized to 3,4-dihydroxyphenylacetic acid (DOPAC) via aldehyde dehydrogenase (ALDH). As a minor and compensatory metabolic pathway, DOPAL can be reduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 43 publications
3
127
0
Order By: Relevance
“…Moreover, various studies reported that the exposure to radiation induced oxidative damage in several organs (Bhatia and Manda 2004;Hassan et al 2010, Wang et al 2010) and mitochondrial membranes (Kamat et al 2000). Moreover, the oxidative stress linked to dopaminergic neurons damage might be owned to lipid peroxidation products 4-hydroxynonenal (4HNE) and malondialdehyde (MDA) which inhibit the aldehyde biotransformation step of DA catabolism to 3,4-dihydroxyphenylacetic acid (DOPAC) yielding elevated levels of the endogenous neurotoxin 3,4-dihydroxyphenylacetaldehyde (DOPAL), which is more toxic to dopaminergic neurons than DA quinones (Jinsmaa et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various studies reported that the exposure to radiation induced oxidative damage in several organs (Bhatia and Manda 2004;Hassan et al 2010, Wang et al 2010) and mitochondrial membranes (Kamat et al 2000). Moreover, the oxidative stress linked to dopaminergic neurons damage might be owned to lipid peroxidation products 4-hydroxynonenal (4HNE) and malondialdehyde (MDA) which inhibit the aldehyde biotransformation step of DA catabolism to 3,4-dihydroxyphenylacetic acid (DOPAC) yielding elevated levels of the endogenous neurotoxin 3,4-dihydroxyphenylacetaldehyde (DOPAL), which is more toxic to dopaminergic neurons than DA quinones (Jinsmaa et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation products interfere with detoxification of DOPAL (39) by inhibiting aldehyde dehydrogenase and aldehyde reductase (40), stimulating a potentially deadly positive feedback loop. Consistent with a pathogenetic role of catecholaldehydes in Lewy body diseases, a recent postmortem study noted a high ratio of DOPAL/DA in the putamen of patients with end-stage PD (41).…”
Section: Figurementioning
confidence: 99%
“…Enzymatic deamination of monoamines generates hydrogen peroxide, which by way of reaction with metal ions produces toxic hydroxyl radicals. Moreover, lipid peroxidation products inhibit aldehyde dehydrogenase and aldose/ aldehyde reductase, interfering with the detoxification of the aldehydes [27]. Importantly, the aldehyde produced by enzymatic deamination of cytosolic dopamine, dihydroxyphenylacetaldehyde (DOPAL), potently oligomerizes alpha-synuclein in vitro and precipitates alpha-synuclein in catecholaminergic cells [28], possibly inducing destabilizing positive feedback loops.…”
Section: The Monoamine Aldehyde Hypothesismentioning
confidence: 99%